Oppositional defiant disorder dimensions and subtypes among detained male adolescent offenders. (23rd October 2015) - Aebi, Marcel; Barra, Steffen; Bessler, Cornelia; Steinhausen, Hans‐Christoph; Walitza, Susanne; Plattner, Belinda
Abstract : Background: In adolescent offenders, oppositional defiant disorder (ODD) and its dimensions/subtypes have been frequently ignored due to the stronger focus on criminal behaviours. The revised criteria of the DSM‐5 now allow diagnosing ODD in older youths independent of conduct disorder (CD). This study aimed at analysing ODD dimensions/subtypes and their relation to suicidality, comorbid psychiatric disorders, and criminal behaviours after release from detention in a sample of detained male adolescents. Methods: Suicidality and psychiatric disorders (including ODD symptoms) were assessed in a consecutive sample of 158 male adolescents ( M age = 16.89 years) from the Zurich Juvenile Detention Centre. Based on previous research findings, an irritable ODD dimension and a defiant/vindictive ODD dimension based on ODD symptoms were defined. Latent Class Analysis (LCA) was used to identify distinct subtypes of adolescent offenders according to their ODD symptom profiles. Logistic regression and Cox regression were used to analyse the relations of ODD dimensions/ODD subtypes to comorbid psychopathology and criminal reoffenses from official data. Results: The ODD‐irritable dimension, but not the ODD defiant/vindictive dimension predicted comorbid anxiety, suicidality and violent reoffending. LCA identified four subtypes, namely, a no‐ODD subtype, a severe ODD subtype and two moderate ODD subtypes with either defiant or irritable symptoms. The irritable ODD subtype and the severe ODD subtype were related to suicidality and comorbid affective/anxiety disorders. The irritable ODD subtype was the strongest predictor of criminal (violent) reoffending even when controlling for CD. Conclusions: The present findings confirm the presence of ODD dimensions/subtypes in a highly disturbed adolescent offender sample. Irritable youths were at risk of suicide and persistent criminal behaviours. Due to the severe consequences of irritability, a standardized assessment approach and a specific treatment is needed in prison to prevent suicide among the detainees and further harm to the society. As defined in the DSM‐5, the present findings confirm the validity of ODD and ODD dimensions/subtypes as a diagnostic category among older youths.